(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
Understanding that the essential subject matter of psychology is not an object, thing or self-enclosed entity, this article presents the Buddhist psychology of non-self as a phenomenology of self-experiencing. Through the dizzying interaction of five psychic constituents (skandhas), emotional reactivity and mental fixation reify a self-entity where there is none.